Drama Kings : Players and Publics in the Re-creation of Peking Opera, 1870-1937. - Goldstein, Joshua, 1965- (University of California Press, 2007)
Describes the formation of the Peking opera in late Qing and its subsequent rise and re-creation as the epitome of the Chinese national culture in Republican era China. This book looks into the lives of some of the opera's key actors, and explores their methods for earning a living, and their status in an ever-changing society.